Impacto del material didáctico en el rendimiento escolar de los estudiantes del tercer año de educación general básica de la Escuela Aurora Estrada de Ramírez recinto Tres Postes, cantón Jujan, Provincia del Guayas - Montalvo Fajardo, Jesus del Carmen (2019)
The different types of didactic materials have been gaining increasing importance in education. Since it functions as an instrumental mediator and influences the value education from an early age, the didactic material is used to support the development of students in aspects related to thinking, oral and written language, imagination, and socialization, better knowledge of oneself and of others expressing a pedagogical proposal. The objective of this research work is to establish the impact of the didactic material on the school performance of students of the third year of general basic education of the school "Aurora Estrada de Ramírez" Tres Postes canton, Jujan canton, Guayas province, the interview and the observation technique. The results indicated that the use of teaching materials has a direct and significant influence on the students' academic performance, allowing for better knowledge acquisition and motivating students towards more effective learning. It was also possible to determine that the teaching materials that exist in the Aurora Estrada de Ramírez Basic Education School are simple and / or traditional such as books, flipcharts, sheets, summaries. There is a lack of sophisticated materials such as audiovisual materials that serve to present images, which can be seen in the statistical tables of the surveys made to students.